PENGARUH JAMINAN SOSIAL, SELF EFFICACY DAN SERVANT LEADERSHIP TERHADAP KOMITMEN ORGANISASI DAN KINERJA KARYAWAN RUMAH SAKIT ISLAM NASHRUL UMMAH LAMONGAN - Bayu Aji Harsanto; Nanis Susanti (Media Mahardhika, 2021)
This study aims to find out and analyze the effect of social security, self-efficacy and servant leadership on organizational commitment and its impact on employee performance at RSI (Rumah Sakit Islam) Nashrul Ummah Lamongan. This study uses a quantitative descriptive approach using data analysis based on empirical theory between the variables in this study, then data is collected by questionnaire instrument. To analyze the data, The Structural Equation Modeling (SEM) was used from the AMOS statistical software. The total population sampling method with total population of 240 employees. The results of this study indicate that Social security, Self-efficacy, and Servant Leadership berpengaruh positif dan signifikan terhadap komitmen, sedangkan social security has no significant effect on employee performance, likewise Self-efficacy and servant leadership has a positive and significant effect on employee performance, . Furthermore Organizational commitment has a positive and significant effect on employee performance.